The association between obesity-related legislation in the United States and adolescents' weight - Annita Kobes; Tina Kretschmer; Margaretha C. Timmerman (Elsevier, 2022)
Effective obesity prevention requires intervening at all levels of society, including the governmental level. Policy interventions at the governmental level are especially promising as they tend to involve minimal individual effort while, at the same time, reach many people. The amount of state-level obesity-related legislation in the United States has increased over the years, and several laws were installed in contexts that reach young people, such as schools. Given this increase in state-level obesity-related legislation targeting youth, we tested whether the quantity of obesity-related legislation in U.S. states was associated with adolescent BMI and overweight/obesity prevalence. Linear and multilevel analyses showed that the quantity of physical activity-related legislation was associated with lower overweight/obesity prevalence yet with very modest effect size (b = -0.002, p = .042). Our results underline the likely importance of obesity-related legislation. In addition, the value of examining both BMI and overweight/obesity prevalence when evaluating interventions is demonstrated.